Clinical flexible needle puncture path planning based on particle swarm optimization. (September 2020) - Cai, Chenxu; Sun, Chunsheng; Han, Ying; Zhang, Qinhe
Abstract: Background and objective: Percutaneous puncture with flexible needle has important value in clinical application for its low trauma and flexible path. However, it is difficult to guarantee accuracy and avoid obstacles in puncture process. Therefore, developing a viable path planning method is particularly important. In this research, the bending deformation law of flexible needles during puncture was studied and the puncture path was planned to provide a feasible method for clinical application of flexible needles. Methods: According to the researchs that have been conducted, the path of the flexible needle in the tissue could be considered as a circular arc stitching. This research studied the calculation method of arc radius and obtained its actual value by the puncture experiments. Based on the arc model, the spatial transformation method of three-dimensional path planning was studied. In addition, a simplified particle swarm optimization (PSO) was applied into the process of path planning by changing the central angle of arc and the rotation angle of the needle body. Results: The results of Experiment 1 showed that the path radius of the flexible needle pierced into gelatin prosthesis was influenced by four parameters, which were needle diameter, tip angle, puncture speed and the weight ratio of gelatin powder. As the needle diameter and tip angle increased, the radius of needle path tended to increase, but when the puncture speed and gelatin mass ratio increased, the radius of needle path decreased. The results of Experiment 2 showed that the distances of needle tip apart from target point were 3.2 mm (barrier-free experiments) and 1.8 mm (obstacle experiments). Conclusions: This research links the intelligent algorithm with the flexible needle puncture tissue process, which has high value in future clinical application. By setting the correct boundary conditions and parameters, the flexible needle can be planned to reach the target point accurately.